An evaluation of invertebrates for use as success indicators for minesite rehabilitation - Majer, Jonathan; Bisevac, L. (1999)
Success Indicators, also known as Completion Criteria, are measures used to help identify when minesite rehabilitation has reached a sufficient standard that it can be relinquished by the mining company. The most common approaches to using such criteria are based on physical, edaphic and vegetation characteristics . Invertebrates are seldom, if ever, included; they are simply presumed to return with the re-establishment of flora and vertebrate animals.This is an unfortunate viewpoint since Invertebrates are ideally suited for conveying information about the environmental health of an area. There is therefore an opportunity to use measurements on invertebrates as indicators of the success of rehabilitation and to include these in the schedule of success indicators. This paper makes a comparison of the logistics of performing: 1) vegetation, 2) vertebrate and 3) invertebrate surveys in the monitoring ofrehabilitation success. It presents evidence that Invertebrates can provide a cost-effective means of generating information on the environmental status of minesites undergoing rehabilitation.